2004
DOI: 10.1023/b:biry.0000040205.77734.d8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Phosphospecific Antibodies for Monitoring Phosphorylation of Proteins Encoded by the Myosin Light Chain Kinase Genetic Locus

Abstract: Myosin light chain kinase (MLCK) and the kinase-related protein (KRP), also known as telokin, are the major independent protein products of the smooth muscle/non-muscle MLCK genetic locus. They share a common C-terminal part and major sites phosphorylated in vivo. Whereas MLCK is critically involved in myosin activation and contraction initiation in smooth muscle, KRP is thought to antagonize MLCK and to exert relaxation activity. Phosphorylation controls the MLCK and KRP activities. We generated two phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Due to the lack of space, we will not analyze either effects of phosphory lation and dephosphorylation of myosin light chains or the role of caldesmon (or calponin) in regulation of smooth muscle contraction. These problems are thor oughly described in a number of recently published reviews [17,25,30,37,52]. Let us analyze only the effect of Hsp20 on the regulation of smooth muscle contrac tion.…”
Section: Figmentioning
confidence: 99%
“…Due to the lack of space, we will not analyze either effects of phosphory lation and dephosphorylation of myosin light chains or the role of caldesmon (or calponin) in regulation of smooth muscle contraction. These problems are thor oughly described in a number of recently published reviews [17,25,30,37,52]. Let us analyze only the effect of Hsp20 on the regulation of smooth muscle contrac tion.…”
Section: Figmentioning
confidence: 99%
“…In this study, seven of the identified phosphorylation sites were not predicted by any of the five web servers. Ser1776 and Ser1779 were earlier identified as PKA sites in smMLCK by Krymsky et al (23) and, later, Khapchaev et al (45) showed that Ser1779 is subject to mitogen-activated protein kinase phosphorylation site and Ser1773 is a PKA phosphorylation site corresponding to nmMLCK. In this study, we were not able to clarify PKA phosphorylation sites on S1776 or S1779 due to a lack of MS 3 data.…”
Section: Discussionmentioning
confidence: 95%
“…The polyclonal antibodies to KRP [22] and KRP phosphorylated at Ser 13 and Ser 19 [27] have been described. The anti-rMLC antibody (clone Y-21) and microcystin-LR were from Sigma, USA.…”
Section: Methodsmentioning
confidence: 99%
“…GST-tagged mitogen-activated protein kinase with a molecular weight of 44 kDa (p44 erkl -MAP kinase) expression and activation by phosphorylation with the constitutively active His 6 -tagged MAPK/ERK (extracellular-signal-regulated kinase) kinase 1 (MEK1) were performed as described [27]. The plasmid pET22-b+/DD-hKRP, expressing the phosphorylation-mimicking KRP mutant, S13D,S19D, was generated using the pET22-b+/hKRP construct encoding the full-length human KRP [27] as a template.…”
Section: Plasmids and Molecular Cloningmentioning
confidence: 99%
See 1 more Smart Citation